Morphological analysis of the human maxillary sinus using three-dimensional printing - Nadia Araneda; Marcelo Parra; Wilfredo A González-Arriagada; Mariano Del Sol; Ziyad S Haidar; Sergio Olate (Wolters Kluwer Medknow Publications, 2019)
Background: The maxillary sinus (MS) is described as a pyramid-shaped cavity of the maxilla. Aim: The aim of this research is to present a strategy for morphological analysis of the MS using three-dimensional (3D) printing acquired through cone-beam computed tomography images. Material and Methods: A cross-sectional exploratory, single-blind study was conducted, including 24 subjects. MSs were reconstructed, and 3D virtual modeling was done bilaterally, obtaining 48 physical models generated on a 3D printer. The statistical analysis used tests of normality and tests using a value of P < 0.05 to establish statistical significance. Results: The mean of the MS volume was 15.38 cm3 (±6.83 cm3). The minimum volume was 5.4 cm3 and the maximum was 30.8 cm3. In a bilateral comparison of the right and left volume of the same individual, there were no significant differences (P = 0.353). In relation to the morphology of the MSs, the most prevalent was pyramidal with a square base with a prevalence of 66.7%. Related to gender, significant differences were observed only for the left volume (P = 0.009), with the mean volume being significantly greater in the men (19.69 cm3) than in the women (12.28 cm3). Conclusion: 3D printing of the MS permitted the more precise observation of anatomical features that cannot be seen on a 2D screen. A classification is presented that allows an analysis of sinus morphology, although it is necessary to conduct studies with larger samples to obtain more conclusive results.